Practical radiation protection and applied radiobiology - Dowd, Steven B. (W. B. Saunders, 1999)
The latest edition of this text presents both theory and clinical practice of radiation protection and radiobiology -- from X-ray production and nuclear medicine to radiation therapy. Updated to reflect recent regulations, this text serves as a complete review for national certification exams as well as a useful review for clinical practice.